2014
DOI: 10.4184/asj.2014.8.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Oswestry Disability Index and Magnetic Resonance Imaging Findings in Lumbar Canal Stenosis: An Observational Study

Abstract: Study DesignCross-sectional study.PurposeThe aim of the study was to determine relationship between the degrees of radiologically demonstrated anatomical lumbar canal stenosis using magnetic resonance imaging (MRI) and its correlation with the patient's disability level, using the Oswestry Disability Index (ODI).Overview of LiteratureThe relationship between the imaging studies and clinical symptoms has been uncertain in patients suffering from symptomatic lumbar canal stenosis. There is a limited number of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…The correlation between radiological and clinical findings to distinguish between symptomatic and asymptomatic patients is, however, limited and unreliable for all common modalities such as X-ray, computed tomography, MRI scan or single-photon emission computed tomography (SPECT) scan [ 32 35 ]. This applies to both facet joint degeneration [ 36 , 37 ] and spinal stenosis, independent of whether quantitative [ 38 , 39 ] or qualitative stenosis classifications [ 40 ] are used. Clear correlations are usually described only for different parameters of the same technique: the occurrence of intraarticular fluid of the facet joints, for example, is known to increase with degenerative spondylolisthesis [ 41 , 42 ] and appears to be associated with lumbar instability [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between radiological and clinical findings to distinguish between symptomatic and asymptomatic patients is, however, limited and unreliable for all common modalities such as X-ray, computed tomography, MRI scan or single-photon emission computed tomography (SPECT) scan [ 32 35 ]. This applies to both facet joint degeneration [ 36 , 37 ] and spinal stenosis, independent of whether quantitative [ 38 , 39 ] or qualitative stenosis classifications [ 40 ] are used. Clear correlations are usually described only for different parameters of the same technique: the occurrence of intraarticular fluid of the facet joints, for example, is known to increase with degenerative spondylolisthesis [ 41 , 42 ] and appears to be associated with lumbar instability [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result also showed that NCOS is more responsive than ODI in measuring functional outcome. A study conducted by Goni et al reported that ODI questionnaire was easily comprehended and had a response rate of 91% in patient with low back pain but not predictive for the underlying patho-morphology [12] . Another study by Azimi et al on the use of NCOS for lumbar canal stenosis patients with neurogenic claudication showed that NCOS is a reliable and valid instrument for measuring functionality with coefficient 0.77 and 0.91 at pre-and post-operation [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, more than 80% of elderly individuals experience musculoskeletal pain, and the prevalence of pain increases with age 8,9) . Moreover, degenerative spinal disorders also increase with age as well 10) . Furthermore, the number of females with low back pain, for which there is a high rate of complaints in the comprehensive survey of the living conditions as is also the case with NSP, increases with age 2) .…”
Section: Introductionmentioning
confidence: 99%